Sarilumab monotherapy compared with adalimumab monotherapy for the treatment of moderately to severely active rheumatoid arthritis: an analysis of incremental cost per effectively treated patient - Fournier M; Chen C; Kuznik A; Proudfoot C; Mallya UG; Michaud K (Dove Medical Press, 2019)
Marie Fournier,1 Chieh-I Chen,2 Andreas Kuznik,2 Clare Proudfoot,3 Usha G Mallya,4 Kaleb Michaud5,6 1Health Economics & Value Assessment, Sanofi France, Chilly-Mazarin, France; 2Regeneron Pharmaceuticals, Inc., Tarrytown, NY, USA; 3Sanofi, Guildford, UK; 4Sanofi, Bridgewater, NJ, USA; 5University of Nebraska Medical Center, Omaha, NE, USA; 6The National Databank for Rheumatic Diseases, Wichita, KS, USA Purpose: Treatment outcomes and direct medical costs were examined, from a US health payer perspective, of monotherapy with sarilumab 200 mg subcutaneous (SC) every 2 weeks (Q2W) vs adalimumab 40 mg SC Q2W/QW in adult patients with moderately to severely active rheumatoid arthritis who are intolerant of, inadequate responders to, or considered inappropriate candidates for continued methotrexate treatment.Patients and methods: Short-term analysis was based on 24-week wholesale acquisition costs of drugs and treatment response observed in the MONARCH Phase III trial (NCT02332590) per American College of Rheumatology (ACR) 20/50 criteria and European League Against Rheumatism (EULAR) Moderate/Good Disease Activity Score 28-joint count erythrocyte sedimentation rate. Long-term analysis, which also considered drug administration and routine care costs, was conducted via a 6-month decision tree and a 1- to 10-year Markov model with microsimulation of patient profiles from the MOBILITY Phase III trial (NCT01061736). Utilities and quality-adjusted life-years (QALYs) were estimated by mapping 6-month ACR levels to a relative change in Health Assessment Questionnaire – Disability Index score and via published algorithms.Results: For sarilumab and adalimumab, respectively, 24-week drug costs were $18,954 and $29,232, and costs per responder were $26,435 vs $50,055 on ACR20; $41,475 vs $98,425 on ACR50; and $22,511 vs $41,230 on EULAR Moderate/Good. Base case results at 10 years for total costs and QALYs were $176,977 and 2.75 for sarilumab and $212,136 and 2.61 for adalimumab, respectively. Sarilumab was consistently the more effective and cost-saving treatment across all short-term and long-term incremental analyses.Conclusion: Sarilumab monotherapy was the economically dominant treatment on incremental cost per responder and incremental cost per QALY compared with adalimumab monotherapy. These results were maintained within the sensitivity analyses. Keywords: treatment costs, disease-modifying anti-rheumatic drug, IL-6 inhibitor, rheumatoid arthritis, cost per responser